التعليل ودوره في ترشيد السياسة الشرعية - يوسف، عمار Yousuf, Ammar (جامعة بن يوسف بن خدة الجزائر 1 - كلية العلوم الإسلامية - مخبر الشريعة, 2018)
لقد جاء هذا البحث للإجابة عن الإشكالية التالية: هل الأصل في أحكام السياسة الشرعية التعبد أم التعليل؟ وإذا كان الأصل في السياسة الشرعية التعليل، فما دوره في ترشيدها؟ وتبرز أهمية الموضوع في محاولة نقل أصل التعليل من دائرة الجدل الكلامي إلى دائرة النظر الأصولي المقاصدي، من خلال البحث في ماهية التعليل، وتحقيق القول في سبب اختلاف الأصوليين حوله، ومناقشة الظاهرية في إنكارهم لأصل التعليل على جهة العموم، وإيراد الأدلة التي تقرر معقولية أحكام السياسة الشرعية، وأنه لا ينبغي أن تتضمن حكما تعبديا لا ينظر فيه إلى المقاصد والمصالح. والبحث يهدف في نهاية المطاف إلى تفعيل قاعدة التعليل في الفقه السياسي الشرعي باعتباره حلقة وصل السياسة الشرعية بالنظر المقاصدي.
This research came to answer the following problem: Is the origin in the Sharia policy worship or explanation? And if the origin is the explanation, what role does it in its rationalization? The importance of the subject is the attempt to transfer the origin of the reasoning from the circle of philosophic argument to the circle of fundamentalist view of purposes, by looking at what the explanation, and to say the reason of the fundamentalists' divergence around it, and discuss the apparent denial of the origin of the reasoning, and to provide evidence that determine the reasonableness of the sharia policy and that it should not contain an autocratic judgment that does not consider interests. And the research aims at the end to activate the rule of reasoning in the jurisprudence of the sharia politic as a connexion between the sharia policy and Makassid.
Keywords: الفقة الإسلامي -- الشريعة الإسلامية -- المقاصد الفكرية -- الفقة السياسي